Collaborative Dynamic Optimization of New Energy Vehicle Power Battery Recycling and Reuse Strategies Driven by Blockchain - Jing, Hao (Academic Journal of Management Science and Engineering, 2026)
Effective recycling and reuse of retired power batteries have become a critical issue for their sustainable development in the future. Currently, the market for retired power battery recycling is plagued by problems such as mixed recycling channels and lack of information transparency. Blockchain offers solutions for the full life-cycle management of power batteries. Thus, how to leverage blockchain to promote the efficient recycling and reuse of retired power batteries has emerged as a key issue. Considering two recycling channels and reuse modes empowered by blockchain, this paper establishes long-term dynamic decision-making models of the power battery closed-loop supply chain (PB-CLSC) using differential game, derives the feedback equilibrium strategies of all stakeholders. Furthermore, the impact of different recycling and reuse strategies with blockchain is thoroughly investigated, identifying the optimal recycling and reuse strategies.
Keywords: Power Battery Closed-loop Supply Chain; Blockchain Technology; Reuse Mode; Recycling Channel; Differential Game